Study on the micro mechanism of shale self-sealing and shale gas preservation - Xusheng GUO; Dongfeng HU; Lingjie YU; Longfei LU; Chencheng HE; Weixin LIU; Xiancai LU (Shiyou shiyan dizhi, 2023)
In order to accelerate the exploration and development of shale gas, this paper elaborates on the micro mechanism of shale gas preservation based on shale self-sealing. The self-sealing capacity of shale formations is mainly related to the low connectivity of nano-throats, low speed diffusion caused by bound water occurrence, capillary force sealing, and breakthrough pressure along the layer direction under burial conditions. Results of analysis based on shale pore morphology and connectivity show that the organic pores in shale are mainly composed of nano-throats with poor connectivity and significant retention effects. At the same time, the stacking of multiple relatively dense sealing layers within the top, bottom, and shale layers is conducive to self-sealing in longitudinal direction. Based on experimental and molecular dynamics simulation analysis of the influence of bound water on the diffusion and breakthrough pressure of the shale matrix, it is revealed that the bound water occurrence significantly reduces the effective diffusion capacity of shale matrix pores and could cause high capillary forces, leading to effective sealing of the gas stored in organic pores. In the study, the permeability-breakthrough pressure evolution relationship was constructed, revealing that under deep burial conditions, the effective closure of shale bedding fractures along the layer direction can form high breakthrough pressure sealing. During the uplift stage, under relatively weak tectonic compression, the shale could still maintain a high sealing capacity along the layer direction, which is conducive to shale gas preservation. However, under strong tectonic compression, the shale bedding fractures open and communicate with open fault surface, causing the failure of preservation capacity and large-scale loss of shale gas. This study elucidates the microscopic mechanism of shale gas preservation through experiments and molecular dynamics simulations, which could provide useful guidance for marine shale gas exploration in complex structural areas.